Knowledge, attitudes, and practices of pregnant and postpartum women regarding stress urinary incontinence - Qin Dong; Shenxian Wan; Ruihua Wang; Sanshan Guo; Hong Shen; Ningjuan Wang; Wenting Cai; Luxi Cai; Wei Zhao (Scientific Reports)
Abstract This study aimed to assess the knowledge, attitudes, and practices (KAP) of pregnant and postpartum women regarding stress urinary incontinence. Conducted in Suzhou from January to March 2024, the cross-sectional study involved 476 participants, predominantly pregnant women (81.3%). Data were collected through self-administered questionnaires, covering demographic characteristics and KAP scores. Findings revealed median scores: knowledge 20.00 [12.00, 28.00] (range: 0–44), attitudes 21.00 [19.75, 24.00] (range: 8–40), and practices 26.00 [22.00, 31.00] (range: 8–40). Structural equation modeling (SEM) showed knowledge directly influenced attitudes (β = -0.153, p < 0.001), while both knowledge (β = 0.522, p < 0.001) and attitudes (β = -0.128, p = 0.004) significantly impacted practices. Moreover, knowledge indirectly affected practices via attitudes (β = 0.020, p = 0.031). Multivariate logistic regression indicated that higher knowledge scores (OR = 1.101, p < 0.001) and higher education levels were associated with proactive practices. The results highlighted inadequate knowledge and negative attitudes among participants. Consequently, it is vital to implement targeted educational programs aimed at improving understanding and attitudes towards stress urinary incontinence in pregnant and postpartum women, enhancing their self-management behaviors.